Peeta Mellark in The Hunger Games : A Feminist View of “Men Written By Women” - Zhahrin, Mazaya Elsa (Journal Corner of Education, Linguistics, and Literature, 2025)
The term “men written by women” which is a new terminology on the social media platforms namely Tiktok, has sparked conversations revolving on what masculinity is. Peeta Mellark from Suzanne Collins’ The Hunger Games trilogy becomes the embodiment of the "men written by women" trope on social media. “Men written by women” can be considered as a product of the “female gaze”, in opposite of the “male gaze”. The female gaze allows and empowers women writers to challenge and subvert the imposed limitations by the traditional “male gaze” thus resulting in the creation of male characters who defy expectations of the traditional “masculine hero” archetype. This research will examine Peeta Mellark from Suzanne Collins’ The Hunger Games trilogy through a feminist lens, utilizing Connell’s Critical Masculinity Studies, specifically the concept of non-hegemonic masculinity as the primary framework. In addition, this research will examine how Peeta's traits and behaviors which symbolizes the departure from hegemonic masculinity along with the global success of The Hunger games franchise has contributed to the widespread of the “men written by women” trope. The worldwide trend of “men written by women” has enabled women’s agency to redefine on what masculinity is.